Approximation of a solution of boundary value problems for delay integro-differential equations - Cherevko, Ihor; A. Dorosh; I. Haiuk; Cherevko, Igor; Піддубна, Лариса; Piddubna, Larisa (Сучасні проблеми прикладної математики та комп’ютерних наук. Збірник наукових праць, 2021)
In the present note we study an approximate method of solving boundary value problems for delay integro-differential equations based on approximation of the solution by cubic splines with defect two.
Keywords: approximation, solution of boundary value problems for delay, integro-differential equations; solution of boundary value problems for delay; approximation; integro-differential equations